Smart room automatic light controller with visitor counter / Muhammad Faiz Ahmad Fuad, Muhammad Ifny Aliff Suhod and Nor Mohamad Iralimin Nordin - Ahmad Fuad, Muhammad Faiz; Suhod, Muhammad Ifny Aliff; Nordin, Nor Mohamad Iralimin (2013)
We wanted to make something utilities for people, especially for disable person, but I had no clue where to start. Then I have noticed how about make room without switch to turn on/off or we call it automatic room. A lot of people, especially disable or folks person it hard to move to switch on/off the light. So we decide to make final project that automatically switch the light on/off and counting the person coming and leaving the room. This project also can apply in meeting room because it can display the number of person in that particular room. Smart Room Automatic Light Controller with Visitor Counter is designed to save the usage of electrical energy and to avoid wastage. This project takes over the task of automatic switch on and off the light in the room as well as counting the persons in the room precisely. When a person enters the room, the lights are switched on automatically and the counter incremented by one and when a person leaves the room, the counter decremented by one. The lights will be switched off as the last person leaves. IR receiver and IR transmitter sensors are placed at the doors and used to detect the presence of human. In this project, microcontroller AT89C2051 (ATMEL) is used as the brain of the project to make seven segment display function as desired and well all data and information would be process. The output from this sensor sent to the AT89C2051 (ATMEL) microcontroller which then automatic switch on and off via a relay and the numbers of people are displayed using a seven segment display. In addition we use C language to program this AT89C2051 (ATMEL) via Keil software. We use Keil software not MicroC software because Keil software for programming ATMEL and MicroC software for programming PIC. It that new information that we learned in programming Integrated Circuit (IC), so that it will function as desired.